Design and preparation of mixed special wettability fabrics based on backed weave for separation of light oil/water/heavy oil mixtures. (March 2022) - Luo, Meiyin; Yao, Chengjian; Zhai, Shixiong; Jin, Kaili; Huang, XiQin; Zhou, Man; Liu, AiRong; Xu, Bi; Cai, Zaisheng
In recent years, the frequent emission of oily wastewater and marine oil spills has resulted in water bodies containing large amounts of light oil/water/heavy oil mixtures. The increasing pollution of the water prompts us to develop new materials that can separate oil and water effectively. In this work, a mixed special wettability fabric based on the backed weave organization is prepared by using different yarns with special infiltration properties. The mixed special wettability fabric can separate the light oil/water/heavy oil three-phase mixtures successfully in one step, due to the effect of gravity-driven and capillary force-driven. Under the optimal process with the reed number of the fabric 84#, the separation efficiency of water can reach 98.36%, and the average separation flux is 0.447 L/m 2 s. In addition, the mixed special wettability fabric shows a good recycling, as well as structural stability, which is good for the application in practical oil–water separation.